Development of Type 1 Diabetes may occur through a Type 2 Diabetes mechanism - Josefsen, Knud; Krogvold, Lars; Gerling, Ivan C.; Pociot, Flemming; Dahl-Jørgensen, Knut; Buschard, Karsten (Frontiers in Endocrinology, 2022)
Abstract Background: At diagnosis of Type 1 Diabetes (T1D), it has been found that up to 50% of the beta cells are “sleeping”, meaning being alive but inactive. This might provide a promising strategy to reduce destruction due to a virus attack or other beta-cell noxes. The price is, however, that few still active beta cells must be extremely effective in producing insulin and, hence, more vulnerable. Could a more uniform behavior among the islet cells be obtained as early as possibly during the T1D pathogenesis, then the disease process might be stopped. Methods: We analysed various mRNA gene expression in islets from live, newly diagnosed T1D patients from the DiViD study in comparison with healthy human organ donors. From the nPOD study we analysed islets from organ doners with longer duration of T1D, or with type 2 diabetes (T2D). Additionally, a SNP analysis on all the related genes was performed. Findings: What causes the “sleep”? Various possibilities are considered (foetal state, hibernation) but we find a T2D mode of the beta cells most likely. This is supported by the present finding of low levels of insulin receptor mRNA in the islets, known to inhibit insulin production as seen in poorly regulated T2D. Interpretation: This result raises the idea to treat individuals with ongoing T1D development prophylactic with T2D medicine like GLP-1 agonistics, and/or metformin, or others, and maybe combined with anti-immune compounds, in order to wake-up the sleeping beta-cells but also to prevent them dying in an immune attack. Thus, a new paradigm of T2D mechanisms during T1D development could be founded.